Totally fit living : a 30-day program for total health & happiness - Kronomeyer, Robert (Deerfield Beach, Florida : Health Communications, 1996)
Originally published as Syntonics. Englewood Cliffs, NJ : Prentice -Hall, c1994.
Includes appendices, bibliographical references, and indices.
Keywords: Self-actualization (Psychology); Happiness; Health